Application of artificial intelligence in network orchestration system - Tianjiao CHEN; Jiang LIU; Tao HUANG (Dianxin kexue)
Based on software defined networking and network virtualization,network orchestration can deploy differentiated services quickly and efficiently.With the wide application of artificial intelligence technology,the combination of network orchestration system and artificial intelligence has become the research focus of major operators and manufacturers.Firstly,the concept of network orchestration system and the development status of major open source organizations were introduced.Then,based on the design time and the run time,the network orchestration architecture using artificial intelligence was introduced to realize the transformation from “automation” to “intelligence”.Finally,the application of artificial intelligence in SDN,NFV and operation and maintenance in the orchestration system was summarized,and the future development direction was proposed.